2006
DOI: 10.1080/10610270600773006
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and Transport of Alkali and Alkaline Earth Metal Cations byp-tert-Butyldihomooxacalix[4]arene Tetraketone Derivatives

Abstract: The binding properties of three p-tert-butyldihomooxacalix[4]arene tetraketone derivatives (tert-butyl 2b, adamantyl 2c and phenyl 2d) in the cone conformation and one derivative (methyl 2a) in a partial cone conformation, towards alkali and alkaline earth metal cations have been established by extraction studies of metal picrates from water into dichloromethane, stability constant measurements in methanol and acetonitrile, and by 1 H NMR spectrometry. Transport experiments of metal picrates through a dichloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Compounds 2 and 3 were synthesized by using slightly modified procedures previously reported in the literature. [11,16] All titrations (UV/Vis, fluorescence and ITC) were performed by using HPLC-grade CH 3 CN purchased from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 2 and 3 were synthesized by using slightly modified procedures previously reported in the literature. [11,16] All titrations (UV/Vis, fluorescence and ITC) were performed by using HPLC-grade CH 3 CN purchased from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of the studies of alkali and alkaline earth metal cation complexation and transport properties of dihomooxacalix [4]arenes bearing carbonyl groups at the lower rim, we have extended our research into transition and heavy metal ions. [16][17][18][19] This paper reports the binding properties of four tetraketone (methyl 2a, tert-butyl 2b, adamantyl 2c and phenyl 2d) derivatives of p-tert-butyldihomooxacalix [4]arene (1) towards transition (Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ and Zn 2+ ) and heavy (Ag + , Cd 2+ , Hg 2+ and Pb 2+ ) metal cations. These properties have been assessed by extraction studies of metal picrates from an aqueous solution into dichloromethane, transport experiments with the same salts through a dichloromethane membrane and stability constant measurements in methanol and acetonitrile based on UV absorption spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
“…For the ArCH 2 Ar bridges, the variation in chemical shifts experienced by the equatorial methylene protons is downfield and much smaller than that of the axial protons, but the ArCH 2 OCH 2 Ar bridges behave differently, as reported previously [21,26,27]. The axial and equatorial methylene protons of the oxygen bridge move upfield and the equatorial protons experience larger shift variations than the axial ones.…”
Section: Proton Nmr Studiesmentioning
confidence: 52%
“…It has been observed that the chemical shift changes of the methylene protons of the OCH 2 CO groups in dihomooxacalix [4]arene amide [26] and ketones [27,36] derivatives is upfield for the monovalent and downfield for the divalent cations. A closer examination of the spectral changes upon complexation indicates that triamide 1b behaves in a similar way.…”
Section: Proton Nmr Studiesmentioning
confidence: 98%